Electrical Conductivity and Surface Roughness Properties of Ferroelectric Gallium Doped Ba0,5Sr0,5TiO3 (BGST) Thin Films - Irzaman Irzaman; A. Marwan; A. Arief; R.A. Hamdani; M. Komaro (Institut Teknologi Bandung, 2008)
Ba0.5Sr0.5TiO3 (BST) and gallium doped BST (BGST) thin films were successfully deposited on p-type Si(100) substrates. The thin films were fabricated by the chemical solution deposition (CSD) and spin coating method, with 1.00 M precursor and spinning speed of 3000 rpm for 30 seconds. The post deposition annealing of the 9 films were carried out BST without gallium (BGST 0%) annealing 850OC, BGST 0% annealing 900OC, BGST 0% annealing 950oC, BGST 5% annealing 850oC, BGST 5% annealing 900oC, BGST 5% annealing 950oC, BGST 10% annealing 850oC, BGST 10% annealing 900oC, BGST 10% annealing 950oC for 15 hour in oxygen gas atmosphere, respectively. The resistance and electrical conductivity of the grown thin films are characterized by I-V converter, meanwhile surface roughness of the grown thin films are characterized by atomic force microscopy (AFM) method. The electrical conductivity of the grown thin films BGST due to semiconductor. The results show that resistance and electrical conductivity of the thin film have strong correlation to the annealing temperature, concentration dopant and surface roughness.